The Role of Organizational Communication and Leadership Style in Conflict Management in Organizational Environments - Rasyid, Aliy; Slamet, Oky; Miftahudin, Miftahudin; Wardhani, Hilda Sari; Fauzobihi, Fauzobihi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the role of organizational communication and leadership style in managing conflict in the organizational environment. By using a qualitative descriptive method, the research conducted is a qualitative descriptive study that aims to find and describe an activity that is carried out.This research is included in the type of library research, namely research whose activities are related to collecting data through literature, or research that explores the object of study by relying on various information from library sources.The results of the study indicate that open, transparent, and inclusive organizational communication can minimize the potential for conflict caused by miscommunication or lack of understanding between individuals or groups. In addition, transformative and participatory leadership styles have proven to be more effective in managing conflict than authoritarian leadership styles. Leaders who are able to listen, provide space for member participation, and make decisions fairly can create a conducive and harmonious work atmosphere.